Al-Qur’an, Hadits, dan Ijtihad Serta Legalitasnya Sebagai Sumber Ajaran Islam - Asnawati; Romlah Abu Bakar Askar (CV. Creative Tugu Pena, 2024)
The sources of Islamic law are everything that becomes the basis for regulating the order of life of Muslims. Most scholars agree that the Koran is the main source of Islamic teachings, then hadith is the second source, and ijtihad is the third source. The Qur'an contains a collection of all the rules for whatever situations and conditions experienced by mankind. Rasulullah SAW as the recipient of the revelation explained the meaning of the Al-Qur'an both in words and deeds. The words and actions of the Prophet are known as hadith. In this way, the Al-Qur'an can be easily implemented by Muslims in their daily lives as a form of obedience to Allah SWT. However, when the Prophet died, there was no longer any place to ask about Islamic law, while world problems continued to develop along with the times, the Qur'an and hadith themselves ordered the ulama to undertake ijtihad to establish a new law for problems that did not exist. The law is in the Koran or hadith. In this way, the ijtihad of ulama is used as the third source of Islamic law. The method in this research is descriptive qualitative research type with library research (library study). The aim of the research is so that readers can know and understand the sources of Islamic teachings so that they are motivated to create a life in accordance with religious guidance.